Micro-computed tomography enhanced cross-linked carboxylated acrylonitrile butadiene rubber with the decoration of new generation conductive carbon black for high strain tolerant electromagnetic wave absorber. (September 2020) - Ghosh, Sabyasachi; Ganguly, Sayan; Maruthi, Avula; Jana, Subhodeep; Remanan, Sanjay; Das, Poushali; Das, Tushar Kanti; Ghosh, Suman Kumar; Das, Narayan Ch.
Abstract: On-demand of flexible and scalable smart composite material for blocking radiation pollution by electronic gadgets is still a challenge for the researchers. Our present work deals with the incorporation of new generation conductive filler (Ketjen 600JD, K-CB) filled carboxylated nitrile butadiene rubber (XNBR). The above composite holds extremely low percolation threshold with high electromagnetic interference (EMI) shielding efficiency (SE) assisted by the absorption dominated shielding mechanism. The electron micrographs have affirmed the distribution and dispersion tendencies of K-CB particles within the matrix phase along with the three-dimensional micro-computed tomography ( μ -CT) scanning. With the addition of only 20 wt % K-CB, the composite shows a percolation threshold value of 7.88 wt % and EMI SE value of 43.39 dB in the X-band frequency range at only 1 mm thickness. Long-term cyclic deformation (including thermal and dynamic) exhibits preservation of flexible K-CB network structure and >95 % retention of EM performance, compared with the other expensive conductive filler incorporated composite materials. In this scenario, our strong belief lies on the promotion of scalable and industrially viable XNBR/K-CB composite which is the new and strong candidate in the emerging field of high strain electromagnetic shielding application in future.